PERAN NINIK MAMAK TERHADAP PENGUASAAN TANAH ULAYAT DI JORONG III KAMPUANG NAGARI GADUT KECAMATAN TILATANG KAMANG KABUPATEN AGAM - Mahya, Reka Repita; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in Jorong III Kampung Nagari Gadut Tilatang Kamang District Agam District. The purpose of this study is to analyze the role of Ninik Mamak in monitoring the ulayat land in Jorong III Kampuang Nagari Gadut Tilatang Kamang District Agam Regency and analyze why the land can be sold. The technique of determining the sample by purposive sampling because the author has set some criteria of the subject that will be used as a source of information in research that will be done as many as 5 (five) people. The author uses qualitative descriptive method and data instrument that is observation, in-depth interview and documentation. The results of this study found that ulayat land belonging to this people can be sold to outsiders because there are several causes, namely the reason for the urgent need, because it can not redeem the previously pawned land, and the next reason is not have a sister (extinct). The role of Ninik Mamak in the control of ulayat land is to preserve the treasures as well as to preserve, explain to the child's nephew in all heritage treasures of his own people and supervise in the form of sharing of results. The sale of the land must obtain the agreement of the kaum or all the members of the consent.Keywords: Role, Ninik Mamak, Ulayat Land, Jorong III Kampuang